Research of educational resources equilibrium and optimization based on GIS in Northern Zhengzhou - Chen, Qin (2021)
The balanced development of education is one of the important goals of the scientific development of education in China. It has been included in the "National Medium and Long-term Education Reform and Development Plan Outline (2010-2020)". The socialist harmonious society has great practical significance and far-reaching historical significance. However, education balance involves the educational resources on the supply side and the demand-side population of the right age have varying degrees of complexity in terms of time, space, and attribute characteristics, resulting in a series of problems, including how to measure education in a certain area. Whether development is balanced, and how to dynamically monitor whether education is balanced development. GIS (Geographic Information System), as an important tool for space-time analysis, has application potential in solving the above problems. This study selects the three northern districts of Zhengzhou City as the study area, and explores the use of GIS to spatialize and dynamically update them; establish a balanced evaluation index system that covers evaluation indicators in multiple dimensions such as educational opportunities, resource allocation, and education quality. And through a variety of spatial analysis methods such as overlay analysis, buffer analysis, network analysis, etc., quantitatively carry out comprehensive evaluation of education balance in the study area; on this basis, combined with the development of education in the study area in recent years, education is carried out from the perspective of education balance Adjustment and optimization analysis of resource space layout. The main research work of this study includes: (1) Using statistical yearbooks and the Internet, we have obtained multi-source data of residential areas, roads, and traffic related to education balance in the study area, and spatialized processing of related data, including AutoNavi POI (point of interest) data Crawling, spatial distribution of educational resources, spatialization of demographic data. (2) Designed a set of index systems that can evaluate the balance of education in space, including educational opportunities, allocation of educational resources, and educational quality, involving spatial elements such as distance to school, transportation accessibility, and student-teacher ratio, Non-spatial factors such as class allocation and excellent high school admission rate, the combination of the two can quantitatively evaluate the education balance of the three northern districts of Zhengzhou at the street level. (3) Use Location Allocation Model (LA) to carry out education development policy simulation and put forward layout suggestions. Generally speaking, the balanced development level of education in the three northern districts of Zhengzhou City is relatively high in the central urban area. There are still large differences between the urban and suburban areas, and the overall equilibrium degree decreases from the southwest to the northeast. Based on the results of the LA model, it can be seen that at least 14 middle schools must be added in the three northern districts of Zhengzhou to make the school service area to the residential area. The solution results of the comprehensive minimum facilities model can be obtained to optimize the layout of educational facilities in the three northern districts of Zhengzhou. According to the actual needs of the local area, the corresponding educational facilities are equipped to promote the realization of educational balance from the hardware.